Causes and Consequences of Midfacial Hypoplasia in Pigs - Baldwin, Michael Caleb (My University, 2025)
University of Washington Abstract Causes and Consequences of Midfacial Hypoplasia in Pigs Michael Caleb Baldwin Chairs of Supervisory Committee:Susan W. Herring Zi-Jun Liu Department of Orthodontics Midfacial hypoplasia (MFH), or underdevelopment of the upper jaw, nose, and cheek bones, can lead to severe deformity with impairment of breathing. MFH can be life threatening, making treatment imperative, but a lack of understanding about the causes of MFH and how it impairs breathing has limited current treatments. Pigs with MFH served as a new, clinically relevant model for understanding the causes and consequences of MFH. Mild MFH is not uncommon in standard pigs and minipigs, but it is universal and more severe in Yucatan minipigs, making this breed an exceptionally useful model. MFH in pigs is similar to MFH in humans, and pigs better resemble humans in size, anatomy and physiology, and growth than other animal models. The objective of this dissertation was to compare pigs with and without MFH to determine the primary tissue cause of MFH, and to determine whether the structure and function of the nasal and pharyngeal airway in MFH are compromised. Aim 1 tested the hypothesis that the caudal nasal septal cartilage contains an important growth region that ossifies prematurely in MFH pigs, restricting the growth of the midface. The amount and morphology of ossification was measured on computed tomography (CT) images and compared between MFH and normal pigs. The caudal portion of the nasal septum was harvested from normal and affected pigs and examined histologically for chondrocyte replication. MFH pigs had increased ossification, diminishing or even obliterating the cartilage tail, with decreased cell replication and hypertrophy in the caudo-ventral septum. Aim 2 tested the hypothesis that MFH pigs compensate for a short rostrum by increasing the cross-sectional area of their nasal cavity and increasing the size and/or complexity of their conchae to conserve a normal surface area to volume relationship and prevent changes to air conditioning efficiency. Surface area, cross-sectional area, and volume were measured on CT scans. A nasal probe, with dual temperature and humidity sensors, was constructed and used to measure temperature and humidity in the nasal airway. As expected, the cross-sectional area of the nasal airway increased, and the conchae were larger and more complex in MFH pigs. Thus, surface area and volume did not change, and air conditioning was unaffected. Aim 3 tested the hypothesis that MFH constricts the pharyngeal airway due to decreased skeletal space and relative enlargement of the soft tissues. The cross-section of the airway, distance between skeletal restraints, and size of the tongue and soft palate were measured on CT scans. A bulge of tissue on the posterior wall of the pharynx was harvested and examined histologically for tissue properties. The pharyngeal airway was not narrower in MFH pigs, and unexpectedly the nasopharynx was wider. The tissue bulge was composed mostly of fat, which was increased in MFH pigs. In conclusion, the cause of MFH in pigs is related to decreased growth and premature ossification of the caudal nasal septum. Compensation from the conchae conserves surface area to volume in MFH pigs, but the increase in cross-sectional area of the nasal cavity results in a larger nasopharynx and a relatively constricted airway at the site of the bulge, which may predispose MFH pigs to airway obstruction.
Thesis (Ph.D.)--University of Washington, 2025
Keywords: Midfacial hypoplasia; Nasal airway; Nasal probe; Nasal septum; Pharyngeal airway; Pig; Dentistry; To Be Assigned